The The Challenges of Islamic Education in the Digital Age: Moral Crisis, Digital Literacy, and Religious Authority - Milda Amalia; Ruqoyah Arifatul Hasanah (Civiliza Publishing, Indonesia., 2026)
The development of the digital era has brought significant changes in Islamic educational practices. On the one hand, the digital era opens up vast opportunities for access to knowledge and learning innovation, but on the other hand it also presents a variety of serious challenges. This article aims to analyze the challenges of Islamic education in the digital era which include student moral crises, low digital literacy, and shifts in religious authority. The method used in writing this article is a literature review with a qualitative-descriptive approach through the analysis of relevant literature, such as books, journal articles, and credible digital sources. The results show that exposure to unfiltered information, instant culture, and the dominance of social media contribute to the weakening of the internalization of moral values, the low ability to think critically, and the emergence of new religious authorities that do not always have scientific legitimacy. Therefore, Islamic education is needed to revitalize the curriculum, strengthen digital literacy, and rebuild scientific authority based on Islamic values. This effort is expected to be able to make Islamic education relevant and competitive in the midst of digitalization flows.